2012
DOI: 10.5032/jae.2012.01109
|View full text |Cite
|
Sign up to set email alerts
|

Florida Preservice Agricultural Education Teachers’ Mathematics Ability and Efficacy

Abstract: The purpose of this study was to examine the mathematics ability and efficacy of Florida preservice agricultural education teachers. Results indicated that the preservice teachers were not proficient in solving agricultural mathematics problems. On the other hand, the preservice teachers were efficacious in personal teaching efficacy and personal mathematics efficacy, and moderately efficacious in their mathematics teaching efficacy. Additionally, the associations between mathematics ability and mathematics co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
51
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(55 citation statements)
references
References 19 publications
4
51
0
Order By: Relevance
“…The male majority of agriculture teachers in this study was expected and in line with other research (Camp, Broyles, & Skelton, 2002;Foster, 2001), but this trend, combined with the consistent findings that at least half of most teacher preparation students are female, makes gender an important demographic to consider when predicting retention (Stair, Warner, & Moore, 2012;Stripling, Ricketts, Roberts, & Harlin, 2008;Stripling & Roberts, 2012;Wingenbach, White, Degenhart, Pannkuk, & Kujawski, 2007). Ethnicity has been examined with much less frequency in the literature, and it cannot be addressed here either, as the number of minorities participating in this study was so low that the variable could hardly be expected to be part of any predictive model for teacher retention.…”
Section: Discussionsupporting
confidence: 91%
“…The male majority of agriculture teachers in this study was expected and in line with other research (Camp, Broyles, & Skelton, 2002;Foster, 2001), but this trend, combined with the consistent findings that at least half of most teacher preparation students are female, makes gender an important demographic to consider when predicting retention (Stair, Warner, & Moore, 2012;Stripling, Ricketts, Roberts, & Harlin, 2008;Stripling & Roberts, 2012;Wingenbach, White, Degenhart, Pannkuk, & Kujawski, 2007). Ethnicity has been examined with much less frequency in the literature, and it cannot be addressed here either, as the number of minorities participating in this study was so low that the variable could hardly be expected to be part of any predictive model for teacher retention.…”
Section: Discussionsupporting
confidence: 91%
“…Furthermore, the participants averaged 26.5% on the mathematics ability instrument, which indicated the preservice teachers were not proficient in solving agricultural mathematics problems. This disconnect between mathematics efficacy and mathematics ability is consistent with prior research (Stripling & Roberts, 2012a, 2012b, 2013a, 2013b and supports the use of the sample.…”
Section: Target Population and Samplesupporting
confidence: 72%
“…Four studies (Stripling & Roberts, 2012a, 2013a, 2013b, 2013c were found in the agricultural education literature related to mathematics efficacy and mathematics teaching efficacy. Stripling and Roberts (2012a, 2013a, 2013b found preservice teachers at the University of Florida were efficacious in personal mathematics efficacy and moderately efficacious in mathematics teaching efficacy. Furthermore, Roberts (2013a, 2013b) found the incorporation of mathematics teaching and integration strategies based on the Math-in-CTE model (Stone, Alfeld, Pearson, Lewis, & Jensen, 2006) into an agricultural education teaching methods course did not significantly affect mathematics efficacy or mathematics teaching efficacy.…”
Section: Preservice Agricultural Education Teachersmentioning
confidence: 99%
See 1 more Smart Citation
“…Stripling and Roberts (2012) used self-efficacy as the framework in a study of Florida preservice agricultural education teachers' math ability. Selfefficacy framed a study on Oklahoma agricultural education teachers' use of interactive whiteboards (Bunch, Robinson, & Edwards, 2012).…”
Section: Theoretical Frameworkmentioning
confidence: 99%